Drug Reactions Seen Among Patients Admitted to the Dermatology Department - Dertlioglu, Selma Bakar; Cicek, Demet; Coban, Feride Gul; Halisdemir, Nurhan (Deri Zuhrevi Hastaliklar Dernegi, 2012)
Background and Design: The purpose of this study was to evaluate the drug reactions observed in patients who applied to Dermatology Department and to determine which drugs caused these reactions, the type of the reactions and their frequency. Materials and Methods: A total of 193 patients admitted to the Dermatology Department with the diagnosis of drug reaction between January 2008 and December 2009 were retrospectively evaluated. Age, sex, symptoms, laboratory tests, diagnosis and treatment information were obtained by examining the patient record forms. Results: During the period of twenty-four months, 193 patients were admitted to the Dermatology Department 107 (55.4%) of them were female and 86 (44.6%) were male. The patients were aged between 8 month and 80 years with a mean age of 37.00 +/- 2.5 years. The duration from drug intake to the development of lesions ranged from 15 minutes to 1 year. The most common drug reaction was urticaria (72 patients) and the other reactions were maculopapular drug eruptions (31 patients), fixed drug eruption (24 patients), and pruritus (14 patients). The most common drugs held responsible were antibiotics (63 patients, 32.6%) followed by analgesics (37 patients, 19.2 %), and antihypertensive drugs (19 patients, 9.8%). Twenty-nine patients (15.0%) were diagnosed histopathologically. Nineteen patients had mild transaminase elevation, while no complications were detected in the other systems. The drug reactions were accompanied by atopy in 26 patients. Conclusion: Based on the results of the present study, the most common drug reactions are urticaria-angioedema, maculopapular eruption, and fixed drug eruption and the most frequent causative agents are antibiotics, analgesics, and anti-hypertensive drugs.
Dermatoloji poliklini?ine başvuran hastalarda gözlenen ?laç reaksiyonlari
Keywords: Drug reactions; urticaria; antibiotics